Kawasaki Disease and Allergic Diseases - Huang, Po-Yu; Huang, Ying-Hsien; Guo, Mindy Ming-Huey; Chang, Ling-Sai; Kuo, Ho-Chang (Frontiers in Pediatrics, 2021)
Abstract Background Kawasaki disease (KD) is an inflammatory disorder with an unknown etiology. It is the leading cause of acquired heart disease, which leads to coronary vasculitis among children. Studies of frequent manifestation of allergic diseases in children with KD have been the subject of mounting clinical interest. However, evidence supporting the association between KD and allergies has yet to be systematically reviewed. Methods In this article, we reviewed current literature regarding the association between KD and allergic diseases. References for this review were identified through searches of PubMed, Cochrane, and Embase through the end of August 2020. Results The results of the analyses of immune repertoire, clinical, and epidemiological studies have indicated some of the characteristics of infectious disease for KD. Although some allergic disorders, such as asthma, may be exacerbated by viral infections, allergies are typically caused by an allergen that triggers an immune response, with the potential involvement of type 2 inflammation and immune disturbances leading to tissue remodeling in genetically susceptible hosts. The effect of intravenous immunoglobulin is multi-faceted and results in a decrease in activating Fc gamma receptor IIA and an increase in anti-inflammatory eosinophils. The findings from this review demonstrate that children who have suffered from KD are more likely to have allergic rhinitis than the general population and their siblings, a condition that lasts until the age of 17. When followed up as teenagers and adults, children with KD are more likely to develop urticaria. Conclusions This review supports that allergic diseases, such as allergic rhinitis, have been demonstrated to increase following KD. Therefore, the importance of allergic diseases in patients with KD should be emphasized in long-term care. Interventions that include strategies for managing allergies in children with KD would be beneficial.